2009
DOI: 10.1128/iai.01518-08
|View full text |Cite
|
Sign up to set email alerts
|

Independence ofAnaplasma marginaleStrains with High and Low Transmission Efficiencies in the Tick Vector following Simultaneous Acquisition by Feeding on a Superinfected Mammalian Reservoir Host

Abstract: Strain superinfection occurs when a second pathogen strain infects a host already carrying a primary strain. Anaplasma marginale superinfection occurs when the second strain carries a variant repertoire different from that of the primary strain, and the epidemiologic consequences depend on the relative efficiencies of tick-borne transmission of the two strains. Following strain superinfection in the reservoir host, we tested whether the presence of two A. marginale (sensu lato) strains that differed in transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…This conclusion is supported by progressive analysis of variant composition: (i) animals with naturally acquired superinfection had a statistically significantly greater number of unique Msp2 sequences than animals either experimentally infected with single strains or infected with a single strain naturally, (ii) the greater number of unique sequences reflected a statistically significant increase in primary structural diversity in the superinfected animals, and (iii) the increase in primary structural diversity reflected increased combinations of the newly identified hypervariable microdomains. These findings under conditions of natural transmission are consistent with those from previous experimental studies in which A. marginale strain superinfection was established when the second strain differed in its msp2 allelic repertoire compared to the primary strain and the unique alleles were expressed by the second strain at the time of superinfection (16,18). The ability to detect all donor alleles and an oligoclonal repertoire of expressed variants using strains for which the complete allelic repertoire has been sequenced provides confidence that the technical approach captured the Msp2 diversity in the experimental infections.…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion is supported by progressive analysis of variant composition: (i) animals with naturally acquired superinfection had a statistically significantly greater number of unique Msp2 sequences than animals either experimentally infected with single strains or infected with a single strain naturally, (ii) the greater number of unique sequences reflected a statistically significant increase in primary structural diversity in the superinfected animals, and (iii) the increase in primary structural diversity reflected increased combinations of the newly identified hypervariable microdomains. These findings under conditions of natural transmission are consistent with those from previous experimental studies in which A. marginale strain superinfection was established when the second strain differed in its msp2 allelic repertoire compared to the primary strain and the unique alleles were expressed by the second strain at the time of superinfection (16,18). The ability to detect all donor alleles and an oligoclonal repertoire of expressed variants using strains for which the complete allelic repertoire has been sequenced provides confidence that the technical approach captured the Msp2 diversity in the experimental infections.…”
Section: Discussionsupporting
confidence: 82%
“…A. marginale subsp. centrale (the Israel vaccine strain) is unique among the A. marginale strains described to date in that it colonizes the tick midgut and salivary gland but replicates at a significantly lower level in the salivary gland (9,25). The numbers of organisms in the salivary gland and saliva at the time of transmission are 10-fold and 30-fold less, respectively, than the numbers of organisms in a high-transmission-efficiency strain (25).…”
mentioning
confidence: 99%
“…The numbers of organisms in the salivary gland and saliva at the time of transmission are 10-fold and 30-fold less, respectively, than the numbers of organisms in a high-transmission-efficiency strain (25). Transmission is correspondingly less efficient and requires Ͼ30-fold more ticks (9,25). This statistically and biologically significant transmission phenotype provides a model for linking gene content and expression with transmission efficiency.…”
mentioning
confidence: 99%
“…Genomic comparison of multiple strains revealed that although A. marginale has a "closed core" genome with essentially the same gene content among all strains, the repertoire of msp2 alleles is distinct (17,18). Importantly, strains with a distinct msp2 allelic repertoire have been shown experimentally to be capable of strain superinfection, in which a second strain establishes infection in an animal already infected with a primary strain (15,19,20). Superinfection requires that the second strain contain at least one unique msp2 allele and that this be expressed at superinfection (19,21).…”
mentioning
confidence: 99%